Pulmonary TB in Pregnancy - Naldi, Efriza; Dewi, Nurmala Sari (Andalas Obstetrics And Gynecology Journal, 2022)
Objective : To report a case of pulmonary TB in pregnancyMethod : A case reportCase : Presented a case of cpulmonar TB in pregnancy on 33-year-old patient. This is fifth pregnancy with twice history of abortion, malnutrition and pulmonary TB (in treatment). The result of chest x-rays was pulmonary TB. The patient was on treatment for anti-tuberculosis drugs for second month. Patient had BMI was 16,88 kg/m2 which is underweight category. There were bronchovesicular and ronchi from both side of lung from auscultation examination. From laboratory findings there was decrease of albumin serum levels to 2,1 gr%. From ultrasound got impression 16-17 weeks of pregnancy. Patient got anti tuberculosis drugs treatment category I incentive phase (2HRZE). During hospitalization treatment, patient was given some nutrition consultation and high calories and high protein diet and also extra 3 egg whites per day. Total calories are 2250 kcal. Patient also got 1 infuse bottle of albumin and albumin supplementation.Discussion : . The incidence of TB in pregnancy was 1/10,000 pregnancies. .. Provision of an appropriate and adequate chemotherapy regimen will improve the quality of life of the mother, reduce the side effects of anti-tuberculosis drugs (OAT) on the fetus and prevent infection in newborns. Patient got anti tuberculosis drugs treatment category I incentive phase (2HRZE) which is no difference theraphy with no-pregnant patient. Patient was not given pyridoxine as adjuvant drugs along with the anti- tuberculosis drugs. Pyridoxine supplementation must be given with the dose  of 50 mg/day and is suggested for every pregnant woman who consumes isoniazid because the deficiency often happens in pregnancy than general population.Conclusion The diagnosis of this patient was correct based on anamnesis, physical examination, and supporting test . Active TB treatment in pregnancy doesn’t have any difference with non-pregnant. The management of this patient is not correct because the patient didn’t get pyridoxine supplementation, didn’t undergo sputum test in second month, and wasn’t done culture M. Tuberculosis as a gold standard.